2016
DOI: 10.1111/pbr.12405
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci associated with grain filling duration and grain number under terminal heat stress in bread wheat (Triticum aestivumL.)

Abstract: Terminal heat stress has the potential negative impact on wheat production across the world, especially in South Asia. Under the threat of terminal heat stress, wheat genotypes with stay green trait would suffer from high temperature stress during their long grain filling duration (GFD). The genotypes with short GFD would be advantageous. To identify quantitative trait loci (QTL) for heat tolerance, a RIL population of K 7903 (heat tolerant) and RAJ 4014 (heat sensitive) wheat genotypes was investigated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…(), Sherman, Martin, Blake, Lanning, and Talbert () and Sharma et al. (). The QTLs for TN were detected on 1B, 5A and 6A in ITMI previously, and they can be reproducibly identified in the present study (Chesnokov et al., ; Kumar et al., ; Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…(), Sherman, Martin, Blake, Lanning, and Talbert () and Sharma et al. (). The QTLs for TN were detected on 1B, 5A and 6A in ITMI previously, and they can be reproducibly identified in the present study (Chesnokov et al., ; Kumar et al., ; Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, temperature and moisture gradients between or among the plots were effectively avoided by means of a hot water radiator‐type heating system and a highly controlled drip irrigation system. Other features that led to improved phenotyping under heat stress included ensuring a uniform plant population through use of a specially designed dibbler (Sharma et al, 2016) and staggered planting to synchronize plant phenology (Pandey et al, 2014; Sharma et al, 2016). Sharma (2015) reported that the desired seed depth and plant spacing could be maintained with greater precision by the dibbling method than by conventional methods such as seed drills or hand sowing.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐three recombinant inbred lines (RILs) were developed through single‐seed descent from a cross between two parental spring wheat genotypes, ‘RAJ4014’ and ‘WH730’. RAJ4014 does not perform well under late‐sown (LS, terminal heat stress) conditions (Pandey et al, 2014; Sharma et al, 2016, 2018), but WH730 is adapted to LS conditions (Rane and Nagarajan, 2004; Pandey et al, 2014; Sharma et al, 2015, 2018). This genotype has been shown to have superior heat tolerance on the basis of its ability to stay green under heat stress (Pandey et al, 2014; Sharma et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations